Methicillin-resistant Staphylococcus aureus contamination in meat and meat products: a systematic review and meta-analysis - Lili Xing; Mao Cheng; Shulei Wang; Jide Jiang; Ting Li; Xinyu Zhang; Jian Yang; Yunlong Tian; Wenjuan Liu (Frontiers in Microbiology)
BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) is distributed all over the world and can easily colonize food animals, which can be transmitted through the food chain, posing a threat to food safety and public health. This study aimed to elucidate the global prevalence of MRSA contamination in meat and meat products via systematic review and meta-analysis.MethodsA comprehensive retrieval was conducted in PubMed, Embase, Web of Science, and the Cochrane Library to identify eligible studies published up to December 10, 2024. Epidemiological data and study characteristics were extracted. Meta-analysis was made using a random-effects model in R software. Subgroup analyses were carried out by meat type, geographical region, and study period. Sensitivity analyses were launched to test the robustness of results, and the trim-and-fill method was applied to assess the potential impact of publication bias.ResultsThe pooled prevalence of MRSA contamination in meat and meat products was 3.72% (95% CI: 2.75–5.02%). The prevalence was 4.46% (95%CI: 2.82–6.98%) in raw poulty meat, 3.86% (95% CI: 2.58–5.74%) in raw livestock meat, and 2.84% (95%CI: 0.55–13.32%) in processed meat products. The Eastern Mediterranean region had the highest MRSA prevalence (9.13%; 95% CI: 4.28–18.44%), while North America reported the lowest (1.89%; 95% CI: 1.30–2.74%). Since 2015, the global prevalence of MRSA was 8.33% (95% CI: 5.29–12.86%). The adjusted pooled prevalence increased to 14.04% (95% CI: 10.38–18.73%) after applying the trim-and-fill method.ConclusionThe presence of MRSA in meat and meat products represents a public health concern. Enhanced surveillance efforts should prioritize raw livestock and poultry meat, particularly in the Eastern Mediterranean and Southeast Asia, to mitigate MRSA contamination in the food supply.Systematic review registrationCRD420251009933, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251009933.